2007
DOI: 10.1021/ma062447j
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Characteristics of Chain Molecules in the Nematic State:  PVT Studies of Main-Chain Liquid Crystal Comprising a Long Oxyethylene-Type Spacer

Abstract: Thermodynamic characteristics of a dimer liquid crystal comprising a relatively long spacer -O(CH 2 -CH 2 O) 6were investigated. The contour length of the flexible spacer (∼25 Å) exceeds that of the hard segments (∼18 Å). The compound exhibits a nematic mesophase (N) between the crystal (C) and the isotropic melt (I) over a sizably wide temperature range (∼80 °C). Thermodynamic quantities such as thermal expansion coefficient R, isothermal compressibility β, thermal pressure coefficient γ ()R/β), and the volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The van der Waals attractive potential effective in the nematic mesophase may be expressed in a generalized form: 25,28,29 …”
Section: General Requirement For the Formation Of Thermotropic Nematimentioning
confidence: 99%
See 1 more Smart Citation
“…The van der Waals attractive potential effective in the nematic mesophase may be expressed in a generalized form: 25,28,29 …”
Section: General Requirement For the Formation Of Thermotropic Nematimentioning
confidence: 99%
“…[30][31][32] In order to optimize the anisotropic interactions ( aniso ðs 2 Þ) in the mesophase, the cooperative bond rotation of the EG segments -OCH 2 -CH 2 Ois inevitable, accordingly the C-C bond being required to pay certain entropy penalty. A recent analysis of mainchain liquid crystals 25,28,29 suggests that (1) flexible segments (spacer) cooperatively participate in the anisotropic attractive interaction by adjusting relative orientation of hard cores, (2) the mitigation of the excessive repulsive interactions may lead to an increase of the volume fraction of unoccupied sites (free volume), and (3) as explicitly indicated by the orientational order parameter of the mesogenic cores, incorporation of the anisotropic interactions aniso ðs 2 Þ causes substantial enhancement of the thermal expansion coefficient in the nematic state. 29 As known from various thermodynamic theories of polymer liquids, is closely related to the free volume of the liquid.…”
Section: General Requirement For the Formation Of Thermotropic Nematimentioning
confidence: 99%
“…It should be noted that the order-disorder characteristics inherent to the primary structure of the flexible spacer are precisely controlled in order to develop the LC mesophase. Combined use of spectroscopic and thermodynamic technique has been extended to treat the trimer models CBA-T9 and CBA-T10, and MBBE-6 [26,38]. As a result, it has been confirmed that 50-60% of the transition entropy (ΔS tr ) p (tr ¼ NI or CN) arises from the variation in the conformational distribution of the spacer at the phase boundary.…”
Section: Comparison With the Constant-volume Transition Entropymentioning
confidence: 97%
“…A comparison between the two different types of spacer, BCBOn (designated as CBA-n in this paper) [25] and MBBE-x with the oxyethylene (OE)-type spacer [26,27] is shown in Fig. 5, where the latent entropy ΔS NI /R is plotted against the number of constituent atoms (n) of the spacer.…”
Section: Rotational Characteristics Of the Bonds Constituting The Spacermentioning
confidence: 99%
See 1 more Smart Citation